PENGARUH KONSENTRASI GEL THEOBROMINE TERHADAP KETAHANAN KEKERASAN PERMUKAAN EMAIL GIGI DESIDUI - indah lestari vidyahayati; Rinaldi Budi Utomo; Indah Titien Soeprihati (Faculty of Dentistry, Universitas Islam Sultan Agung, 2019)
Background: Primary tooth enamel are susceptible to damage because it has a low thickness so it requires preventing treatments to maintain. Theobromine, an alkaloid of the methylxanthine group, has been shown to improve crystallinity and resistance of enamel apatite solubility to acids. The enamel resistance to acid requires a series of test of physical properties, by measuring at microhardness. This study analyzes the eﬀect of theobromine gel consentration on the hardness resistance of primary incisors enamel surfaces.Method: Twenty-fve specimens were divided into 5 groups of topical application of theobromine gel with concentrations of 1%, 2%, 3%, 4%, and 5%, and then immersed in acidic solution. Results were analyzed using one-way ANOVAResult: One-way ANOVA test showed signifcant diﬀerences in the increase and decrease in enamel microhardness after the application of theobromine gel and acid immersion (p <0.05). The highest values of increase and decrease in enamel microhardness (764,74±187,08 VHN and 457,18±54,37 VHN, respectively) was shown in 5% group of theobromine gel.Conclusion: The higher theobromine gel concentration, the higher the microhardness value but unable to maintain the enamel resistance against acid. The 5% theobromine gel concentration was the most eﬀective one to increase the microhardness of primary teeth enamel.